Functional Properties of Gelatin Extracted from Skin of Sole fish (Cynoglossus macrostomus) (Norman, 1928) - Sawant, R. R.; Metar, S. Y.; Koli, J. M.; Nirmale, V. H.; Vishwasrao, V. V.; Temkar, G. S. (Fishery Technology, 2018)
Sole fish (Cynoglossus macrostomus, Norman, 1928) is a major by-catch of shrimp trawl and is a potential source of gelatin. Therefore a study on the extraction and determination of functional characteristics of gelatin obtained from the skin of sole fish was undertaken. Maximum yield obtained from skin of sole fish was 8.32% at 45ºC. The proximate composition of extracted gelatin was found to be comparatively better at 45ºC. The gelatin extracted from the skin had high gel strength at 45ºC than others. Hydroxyproline content was found to be in the range of 5.98-6.57 mg g-1 and highest content of hydroxyproline was obtained at 45°C temperature. Sole fish skin gelatin was found to have lower melting point than mammalian gelatin e.g. bovine and porcine gelatin. These promising finding may contribute to the on-going efforts for using fish gelatin as an alternative source for mammalian gelatins for various applications.